INFLUENCE OF THE ADDITION OF SOYBEAN FLOUR (Glycine max) ON CARP FISH MEATBALLS (Osprhonemus gouramy) TOWARD CONSUMER ACCEPTANCE - Julia Tina; Desmelati Desmelati; Dahlia Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This study was aimed to determine the effect of addition of soybean(Glycine max) flour in carp (Osphronemus gouramy) fish balls on consumer acceptance. The method used in this study was the experimental method, that was a processing of carp fish balls with addition of soybean flour. The design used was a nonfactorial Completely Randomized Design (CRD), namely the addition of soybean flour from the weight of carp meat which consisting of 4 levels: BT0 (without addition of soybean flour), BT1 (10% of soybean flour), BT2 (15% of soybean flour), BT3 (20% of soybean flour). The tested parameters were organoleptic and proximate analysis. The results showed that based on organoleptic analysis that the addition 15% of soybean flour in carp fish balls (BT2) was the best treatment, with the level of consumer acceptance of appearance (97%) with criteria of yellowish and brilliant white, texture value (95%) with solid and compact elasticity criteria, aroma value (91%) with criteria of typical carpfish balls and a little aroma of soybeans, the taste value (98%) with criteria very tasty and distinctive taste of carp and soybean flour.Based on proximate analysis, the value of mositure, ash, protein, fat, and fiber content was 65.9% , 1.8%, 16.1%, 8.68%, and 1.12%, respectively. Keywords:carp, fish balls, soybean flour